Digitonthophagus gazella (Coleoptera: Scarabaeidae): distribution in America and two new records for Colombia - RIVERA, CAROLINA; WOLFF, MARTA (Revista Colombiana de Entomología, 2007)
A literature review is made on the area of distribution of the Indo-African species Digitonthophagus gazella (Coleoptera: Scarabaeidae) since its introduction in 1972 in North America until the present. Its range of dispersion has reached the almost complete colonization of Central America and part of South America. Individuals of this species are also recorded at two new localities of intense cattle ranching in the Caribbean region of Colombia.